Analysis of a-spinasterol Compounds in Trembesi Seeds (Samanea saman (jacq.) Merr) Against Inhibition of 3C-like Protease SARS-CoV-2 Through In Silico Test - Muh. Shofi (Jurnal Sintesis: Penelitian Sains, Terapan dan Analisisnya, 2021)
Coronavirus Disease 2019 or known as COVID-19 is caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). In the virus, there is 3C-like Protease which is a non-structural protein in SARS-CoV-2. These proteins are responsible for the process of translation and viral replication. alpha -spinasterol is a sterol compound in trembesi seeds (Samanea saman (jacq.) Merr) which functions to increase immunity. The purpose of this study was to determine the potential of the alpha-spinasterol compound in trembesi seeds (Samanea saman (jacq.) Merr) as an inhibitor of the 3C-like Protease SARS-CoV-2 with PDB ID: 6M2N using the in silico test. The type of research in this research is computer-based experimental research using in silico tests or molecular docking. The working procedure in this study is molecular docking by comparing the alpha-spinasterol compound in trembesi seeds (Samanea saman (jacq.) Merr) and the comparison compound lopinavir with a protein target of 3C-like Protease SARS-CoV-2 and predicting its physicochemical properties. The results of the in silico test showed that the free bond energy was -8.4 kcal/mol and smaller than the comparison compound lopinavir (-8.2 kcal/mol). The amino acid residues in alpha-spinasterol are Asn203, Gly109, Pro108, Gln107, Gln110, Pro293, and Leu202 which have similar acid residues to lopinavir on compound binding to the 3CL-like Protease from SARS-CoV-2. Meanwhile, based on the Lipinski Rule of Five law, the alpha spinasterol compound still meets the requirements if it will be used as a new drug compound so that alternative drugs can be used to replace lopinavir